(Analysis of the proliferating cell nuclear antigen(PCNA) and Ki-67 as proliferating cell markers) Expressions in colorectal carcinoma at HUSM and its relationship with the duke staging system - Kamal, Meor Zamari Meor; Jaafar, Hasnan; Ali, Kholip; J, Rosli (2001)
Proliferating cell nuclear antigen (PCNA) and Ki-67 are the two important molecules expressed by the proliferating cells. They are important during the DNA synthesis. We applied the antibodies (using DAKO EPOS system) against these two proteins to a series of 54 cases of colorectal adenocarcinoma of various Dukes' stages in order to observe the degree of expressions and their relationship with Dukes' stage. Our study showed, regardless of the Dukes' stage almost all cases are strongly expressed PCNA. However we failed to demonstrate the expression of Ki-67. We conclude that expression of PCNA is strong in colorectal carcinoma but the degree of expression has no relationship with the Dukes' stage. Expression of Ki-67 is probably best seen if we use fresh tissue rather than formalin fixed paraffin embedded tissue.